Carbapenem-resistant Citrobacter freundii harboring blaKPC−2 and blaNDM−1: a study on their transferability and potential dissemination via generating a transferrable hybrid plasmid mediated by IS6100 - Zhang, Feilong; Li, Ziyao; Liu, Xinmeng; Hu, Yanning; Zhao, Jiankang; Zhang, Yulin; Fan, Yanyan; Lei, Zichen; Yang, Xinrui; Li, Zhihua; Li, Chen; Wu, Yongli; et al. (Frontiers in Microbiology, 2023)
The increase in clinical Enterobacteriaceae with dual carbapenemase has become a serious healthcare concern. It is essential to characterize the transferability and potential dissemination of blaKPC-2-and blaNDM-1-coharboring carbapenem-resistant Citrobacter freundii (CRCF).Methods: Four blaKPC-2-and blaNDM-1-coharboring CRCF strains were collected from our surveillance of the prevalence of carbapenem-resistant Enterobacteriaceae. The isolates were assessed using species identification, antimicrobial susceptibility testing, conjugation assays, whole-genome sequencing, plasmid stability, and fitness costs.Clonality, genome, plasmidome, and phylogeny were analyzed to reveal potential dissemination.Results: Three ST523 blaKPC-2-and blaNDM-1-coharboring CRCF strains, collected from the same hospital within one month, exhibited high homology (both identity and coverage >99%), implying clonal dissemination and a small-scale outbreak. Moreover, the blaKPC-2 and blaNDM-1 genes were coharbored on an IncR plasmid, probably generated by a blaKPC-2-harboring plasmid acquiring blaNDM-1, in these three strains.Importantly, the IncR plasmid may form a transferable hybrid plasmid, mediated by IS6100 via transposition, with another IncFII plasmid included in the same C. freundii strain. Furthermore, the blaKPC-2 and blaNDM-1 of the fourth CRCF strain are located on two different non-transferable plasmids lacking complete transfer elements.Additionally, throughout the course of the 10-day continuous passage, the genetic surroundings of blaNDM-1 in four CRCF strains were gradually excised from their plasmids after the eighth day, whereas they maintained 100% retention for blaKPC-2.Genome and plasmidome analyses revealed that blaKPC-2-or blaNDM-1-harboring C. freundii were divergent, and these plasmids have high homology to plasmids of other Enterobacteriaceae.Conclusions: Clonal dissemination of ST523 blaKPC-2-and blaNDM-1-coharboring CRCF strains was detected, and we firstly reported blaKPC-2 and blaNDM-1 concomitantly located on one plasmid, which could be transferred with mediation by IS6100 via transposition. Continued surveillance should urgently be implemented.